Riko The Series: Instilling Honest Character in Early Childhood Through Animated Film - Imara, Faridah Ummu; Turhan Yani, Muhammad; SyaÔÇÖdullah, Achmad (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
Character education in early childhood, especially the value of honesty, is an important aspect in forming a positive personality. This article explores the use of the animated film